Phospholipase C is a novel regulator at the early stages of microspore embryogenesis in Nicotiana tabacum. (31st December 2022) - Luo, Pan; Jiang, Aixi; Zhou, Yi; Yang, Mingchun; Zhou, Xiaotong; Yang, Yong; Yu, Jun; Tang, Xingchun
ABSTRACT: Microspore transfers the developmental fate into embryogenesis in vitro regulated by determinant factors of stress-induced. However, the key regulators of microspore embryogenesis (ME) are still largely undiscovered to reveal the mechanism of cell fate transition. Here, we report that Phospholipase C (PLC) is involved at the early stages of ME in Nicotiana tabacum. NtPLC2/3/4 are expressed at the initial stages of ME. The expression levels of NtPLC2/3 are transient activated after 3 days in culture, while the expression level of NtPLC4 maintains relatively stable. Inhibition of PLCs induces the decrease in NtPLC2/3/4 expression level and decline of ME yield. We confirm that lipids in microspore are degraded and then re-accumulate at first embryonic division stage. Inhibition of PLCs suppresses the lipids metabolism at the early stages of ME. Thus, we propose that PLCs-mediated lipid metabolism is a novel regulator at the early stages of ME.